A Curious Strong Resemblance between the Goldbach Conjecture and Fermat Last Assertion - Nemron, Ikorong Anouk Gilbert (Journal of Informatics and Mathematical Sciences, 2009)
The Goldbach conjecture (see [2] or [3] or [4]) states that every even integer e≥ 4 is of the form e=p+q, where (p,q) is a couple of prime(s). The Fermat last assertion [solved by A. Wiles (see [1])] stipulates that when n is an integer ≥ 3, the equation x^n+y^n=z^n has not solution in integers ≥ 1. In this paper, via two simple Theorems, we present a curious strong resemblance between the Goldbach conjecture and the Fermat last assertion.